The Correlation Between Students’ Vocabulary Mastery and Their Reading Ability at the Tenth Grade Students of SMA Islam Al-Hasyimiyyah Kota Tangerang in Academic Year 2018/2019 - Sintia Dwi Indriyanti; Hery Nuraini (Foremost Journal, 2020)
ABSTRACT The aim of this research was to find the correlation between students' vocabulary mastery and their reading ability at the tenth grade of SMA Islam Al-Hasyimiyyah Kota Tangerang in academic year 2018/2019. This research used quantitative method, all of the population that was 67 students chose by the writer as the sample by using saturated sampling. In collecting the data, the writer made an instrument of vocabulary mastery and reading ability which approximate 40 multiple choices. Because the variable x (vocabulary mastery) was not normally distributed, testing of hypothesis was done by using Kendall's Tau-B test. Based on the calculation, correlation coefficient Kendall's Tau-B for vocabulary mastery and reading ability was 0,310. It means, the correlations between vocabulary mastery and reading ability were good correlation because it closer to 1. The significance value 0,000 < 0,05. It is indicated that Ho is rejected and Ha is accepted. It means that there is significant correlation between vocabulary mastery and their reading ability at the tenth grade students of SMA Islam Al-Hasyimiyyah Kota Tangerang in academic year 2018/2019.